Evidence for genetic and behavioral adaptations in the ontogeny of prehistoric hunter-gatherer limb robusticity. (16th June 2016) - Osipov, Benjamin; Temple, Daniel; Cowgill, Libby; Harrington, Lesley; Bazaliiskii, Vladimir I.; Weber, Andrzej W.
Abstract: Biomechanical analyses of past populations have primarily focused on adults and interpreted variation in limb bone robusticity as indicative of differences in behavior. However, prior to skeletal maturity large changes occur in limb bone robusticity and shape. During ontogeny, the accrual of bone is regulated by differences in genetics and nutrition as well as mechanical loading. We consider how long bone robusticity changes from birth to young adulthood in order to understand when population differences appear during development and why this occurs. We analyzed the femoral and humeral midshafts of four prehistoric hunter-gatherer skeletal samples from four regions: Cis-Baikal, Siberia, Point Hope, Alaska, the central Japanese coast, and the South African Cape. Some statistically significant differences between populations manifest at birth or soon after. Some of this systemic patterning likely reflects adaptation of body shape to climate. Later Stone Age South Africans also appear to demonstrate low limb rigidity residuals as a result of growth towards a unique body type. Differentiation between populations also increases with age, pointing to functional adaptation as a result of behavioral differences. This proves largely concordant with other lines of evidence for differing levels of terrestrial and aquatic mobility in these populations.